Impacts and causative fault of the 2022 magnitude (Mw) 7.0 Northwestern Luzon earthquake, Philippines - Perez, Jeffrey S.; Llamas, Deo Carlo E.; Dizon, Margarita P.; Buhay, Daniel Jose L.; Legaspi, Crystel Jade M.; Lagunsad, Kristine Dionne B.; Constantino, Ryan Christian C.; De Leon, Roland Joseph B.; Quimson, Marc Marion Y.; Grutas, Rhommel N.; Pitapit, Ron Stephen D.; Rocamora, Cyrah Gale H.; et al. (Frontiers in Earth Science, 2023)
At 00:43 UTC on 27 July 2022, a 15-km deep major earthquake with magnitude (Mw) 7.0 struck Northwestern Luzon, Philippines. The strongest ground shaking felt was at PHIVOLCS Earthquake Intensity Scale (PEIS) VII (destructive), equivalent to Modified Mercalli Intensity (MMI) VII, in Abra and along the coastal areas of Ilocos Sur. More than a thousand landslides, rockfalls, slumping and tension cracks were mapped, near the epicentral region, in the northwestern part of the Central Cordillera. Most of the landslides were shallow-seated, many of which were situated along road cuts. Liquefaction manifested as lateral spreads, sand boils, fissures, ground subsidence, and localized swelling was documented along the coastal areas of Ilocos Sur and river channels in Abra and Ilocos Sur. Sea level disturbance was also observed in some coastal areas of Ilocos Sur and La Union. Damages to buildings and infrastructures were documented in areas that experienced PEIS VI (very strong), equivalent to MMI VI and PEIS VII (destructive). Earthquake data, including hypocentral location, aftershock distribution, focal mechanism solutions and strong motion data, and InSAR observation indicate that the earthquake was generated by an almost north-south striking reverse left-lateral oblique fault that is gently dipping to the east. There is no clear indication of a surface rupture based on InSAR analysis and field investigation. The spatial distribution of geologic impacts, such as earthquake-induced landslides and liquefaction, is strongly controlled by the causative fault, the direction of rupture propagation and geology. Peak ground acceleration records (PGA) show a unidirectional rupture propagation and are congruent with the spatial distribution of earthquake impacts. Although earthquake parameters, deformation analysis and field data suggest that the Abra River Fault is the probable causative fault, the derived geometry and kinematics from the seismotectonic analysis challenge our existing understanding of the nature of the Abra River Fault, as well as the other segments of the Philippine Fault. The need to understand these earthquake sources in the country is needed for a better seismic hazard and risk assessment.